Tháng Năm 19, 2024

Rút gọn biểu thức: \( P = \left( {{{3x + \sqrt {9x} – 3} \over {x + \sqrt x – 2}} + {1 \over {\sqrt x – 1}} + {1 \over {\sqrt x + 2}}} \right):{1 \over {x – 1}} \) với \(x \geq 0; \, x \neq 1. \) A \(P= (3\sqrt{x}+1)(\sqrt{x}+1) \) B \(P= (3\sqrt{x}-1)(\sqrt{x}-1) \) C \(P= (3\sqrt{x}-1)(\sqrt{x}+1) \) D \(P= (3\sqrt{x}+1)(\sqrt{x}-1) \)

Rút gọn biểu thức: \( P = \left( {{{3x + \sqrt {9x} – 3} \over {x + \sqrt x – 2}} + {1 \over {\sqrt x – 1}} + {1 \over {\sqrt x + 2}}} \right):{1 \over {x – 1}} \) với \(x \geq 0; \, x \neq 1. \)

A \(P= (3\sqrt{x}+1)(\sqrt{x}+1) \)

B \(P= (3\sqrt{x}-1)(\sqrt{x}-1) \)

C \(P= (3\sqrt{x}-1)(\sqrt{x}+1) \)

D \(P= (3\sqrt{x}+1)(\sqrt{x}-1) \)

Hướng dẫn Chọn đáp án là: C

Lời giải chi tiết:

\( \eqalign{& P = \left( {{{3x + \sqrt {9x} – 3} \over {x + \sqrt x – 2}} + {1 \over {\sqrt x – 1}} + {1 \over {\sqrt x + 2}}} \right):{1 \over {x – 1}} \cr & \,\,\,\, = \left( {{{3x + 3\sqrt x – 3} \over {\left( {\sqrt x – 1} \right)\left( {\sqrt x + 2} \right)}} + {1 \over {\sqrt x – 1}} + {1 \over {\sqrt x + 2}}} \right):{1 \over {x – 1}} \cr & \,\,\,\, = {{3x + 3\sqrt x – 3 + \sqrt x + 2 + \sqrt x – 1} \over {\left( {\sqrt x – 1} \right)\left( {\sqrt x + 2} \right)}}.\left( {x – 1} \right) \cr & \,\,\,\, = {{3x + 5\sqrt x – 2} \over {\left( {\sqrt x – 1} \right)\left( {\sqrt x + 2} \right)}}.\left( {\sqrt x – 1} \right)\left( {\sqrt x + 1} \right) \cr & \,\,\,\, = {{\left( {3\sqrt x – 1} \right)\left( {\sqrt x + 2} \right)\left( {\sqrt x – 1} \right)\left( {\sqrt x + 1} \right)} \over {\left( {\sqrt x – 1} \right)\left( {\sqrt x + 2} \right)}} \cr & \,\,\,\, = \left( {3\sqrt x – 1} \right)\left( {\sqrt x + 1} \right). \cr} \)

Chọn C.